2014
DOI: 10.1017/s1068280500005505
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pasture Insurance on Farmland Values

Abstract: This study examines the impact of publicly supported insurance on agricultural land values. The analysis employs confidential, nationally representative panel data on field-level pastureland values and exploits a natural experiment provided by gradual introduction of the Pasture, Rangeland, and Forage Insurance Pilot Program. We use a field-level fixed-effects model that controls for several time-variant factors. We find that insurance availability is associated with an increase of at least 4 percent in pastur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Conversely, Uzea et al (2014) revealed that risk management tools did not increase debt use. Ifft et al (2014) showed that farm value increased when fields are insured. Kuethe and Morehart (2012) proved that crop insurance improved farmlevel profit in the USA while Zhao et al (2016) did not demonstrate such effect in China.…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Uzea et al (2014) revealed that risk management tools did not increase debt use. Ifft et al (2014) showed that farm value increased when fields are insured. Kuethe and Morehart (2012) proved that crop insurance improved farmlevel profit in the USA while Zhao et al (2016) did not demonstrate such effect in China.…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 99%
“…More specifically, we use difference-in-differences methods and propensity score matching because these methods allow simulating a controlled experiment (Antonakis et al 2010). They have already been used in the literature to measure the effects of crop insurance on debt use (Ifft et al 2015), on profit (Kuethe and Morehart 2012;Zhao et al 2016), and on farm value (Ifft et al 2014). Using this method, we propose to test whether crop insurance purchase has or does not have a negative influence on pesticide expenses and to compare the observed trend with non-insured farmers.…”
Section: Introductionmentioning
confidence: 99%
“…In all other years of this study, the TAEP partial-cost reimbursement program did not significantly affect the price of bulls. This implies that the majority of the $1,200 TAEP partial-cost reimbursement payment was retained by cow-calf producers and not passed along to purebred seed stock producers in the form of higher Ifft, Wu, and Kuethe (2014) observed for pastureland values sold that were eligible for subsidies. The two years when the TAEP payment increased bull prices were the first year of the cost reimbursement payment for bull genetics through TAEP (2006) and when cattle prices were historically high (2015).…”
Section: Resultsmentioning
confidence: 99%
“…While the scale of the programme and its importance have increased over the last 5 years, only a few studies have investigated the RI-PRF programme (e.g. Yu et al 2019;Westerhold et al 2018;Diersen et al 2015;Ifft et al 2014;Nadolnyak and Vedenov 2013). To our knowledge, there is no study that investigates observed patterns in participants' choices of which 2-month intervals to insure.…”
Section: Introductionmentioning
confidence: 99%